Melihat lebih lanjut Knowledge Sharing pada Industri Pengembangan Perangkat Lunak: Sebuah Systematic Literature Review terhadap Faktor-Faktor yang mempengaruhi Knowledge Sharing dan Implementasi Praktisnya - Sofian Lusa; Damayanti Elisabeth; Ariq Naufal Satria; Ringgi Cahyo Dwiputra; Dana Indra Sensuse (AI Society & STMIK Indonesia, 2024)
In an organizational context, effective knowledge sharing can provide significant benefits to the organization. Efficient knowledge sharing can enhance the quality of individuals, thereby automatically improving the overall quality and performance of the organization. This process is particularly suitable for companies engaged in activities requiring complex knowledge, such as software development. However, to implement effective knowledge sharing, a company must possess strong internal capabilities. Furthermore, the forms of knowledge sharing implementation can vary depending on the organization. This research aims to identify the influencing factors of knowledge sharing along with their practical implementations within software development in general using systematic literature review. Several studies were obtained to answer the research questions. The results reveal those 40 distinct factors impacting knowledge sharing behavior individual, organizational, and technological aspects. Additionally, 16 different implementations of knowledge sharing were discovered, with knowledge repositories and meetings as the most common practices.